Coordination pays off: a comparison of two models for organizing hip fracture care, outcomes and costs. (30th April 2014) - Löfgren, Susanne; Rehnberg, Clas; Ljunggren, Gunnar; Brommels, Mats
Summary: Background and purpose: With the "graying" of the population, hip fractures place an increasing burden on health systems and call for efficient forms of care. The aim was to compare two models of organizing hip fracture care at one university hospital working at two sites. The differences in organization were coordinated care provided in one of the sites and traditional care, divided between different institutions, in the other. Material and methods: The study was conducted at a Swedish university hospital and included all 503 hip fracture patients, admitted during the 1‐year period of February 2009 through January 2010. Patient gender, age, type of fracture, admission and discharge dates were documented. The patients were surveyed of their health‐related quality of life at the time of admission and at 4 and 12 months after discharge. The costs for the inpatient care episode were estimated using three costing methods. Results: The coordinated care model resulted in a shorter hospital stay and consistently lower costs. There was no difference between patient‐reported quality of life. Interpretation: The care of hip fracture patients coordinated by a geriatric ward throughout the whole care episode is more cost‐efficient than uncoordinated where patients are transferred to other institutions for rehabilitation. © 2014 The Authors. The International Journal of Health Planning and Management published by John Wiley & Sons Ltd.